2015
DOI: 10.1007/s00248-015-0632-5
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Predictive Functional Analysis of Bacterial Communities in Seawater, Sediment and Sponges in the Spermonde Archipelago, Indonesia

Abstract: In this study, we used a 16S rRNA gene barcoded pyrosequencing approach to sample bacterial communities from six biotopes, namely, seawater, sediment and four sponge species (Stylissa carteri, Stylissa massa, Xestospongia testudinaria and Hyrtios erectus) inhabiting coral reefs of the Spermonde Archipelago, South Sulawesi, Indonesia. Samples were collected along a pronounced onshore to offshore environmental gradient. Our goals were to (1) compare higher taxon abundance among biotopes, (2) test to what extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 94 publications
7
51
0
Order By: Relevance
“…Barott et al (2011) showed clear difference in bacterial community composition of different types of algae and corals. Another recent study from the Spermonde Archipelago confirmed this for a variety of reef sponges (Cleary et al, 2015). The production of specific carbohydrates and antibiotics very likely plays an important role in shaping those stable host-specific microbial communities (Ritchie, 2006; Rosenberg et al, 2007).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Barott et al (2011) showed clear difference in bacterial community composition of different types of algae and corals. Another recent study from the Spermonde Archipelago confirmed this for a variety of reef sponges (Cleary et al, 2015). The production of specific carbohydrates and antibiotics very likely plays an important role in shaping those stable host-specific microbial communities (Ritchie, 2006; Rosenberg et al, 2007).…”
Section: Discussionmentioning
confidence: 70%
“…To date, there are only two studies of the Spermonde Archipelago that have focused on bacterial diversity of settlement tile biofilms (Sawall et al, 2012) and bacterial communities from different reef habitats, specifically within sponges and the functional role of the associated bacteria (Cleary et al, 2015). Our study now further examines the relationship between bacterial communities, habitats, and water quality gradients in the Spermonde Archipelago, and additionally includes mucus of the common hard corals genus Fungia as an important bacterial habitat (Wild et al, 2004; Allers et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Other endophytic bacterial traits predicted by PICRUSt include phosphate solubilization, auxin synthesis and nitrogen fixation features, all of which have been strongly correlated with plant growth. Admittedly, these results can be viewed as supportive as the analysis by PICRUSt does not provide data on actual gene expression in the sample45. The relatively high NSTI scores in root samples indicate not only a degree of uncertainty in the prediction of said gene(s) relevance, but also the novelty of microbes in the endosphere.…”
Section: Discussionmentioning
confidence: 80%
“…One of the most striking examples is the study from Webster et al (2010; Figure 2A ) where bacterial genera such as Iamia , Nitrosococcus , or Trichodesmium shift from less than 0.8% relative abundance in open water to 16.9, 10.8, and 8.3% of the total abundance in sponge microbiota, respectively. These examples are only a small part of the studies reporting such an OTUs abundance shift between seawater or sediment and the sponge microbiota (Lee et al, 2011; Jackson et al, 2012; Cuvelier et al, 2014; O’Connor-Sánchez et al, 2014; Polónia et al, 2014; Reveillaud et al, 2014; Cleary et al, 2015; de Voogd et al, 2015; see Supplementary Figures for more examples).…”
Section: Macroorganisms As Sources Of Rare Taxa For Seawater Microbiamentioning
confidence: 99%